Gastroduodenal Intussusception Due to Pedunculated Polypoid Gastrointestinal Stromal Tumour (Gist): A Rare Case - Prashantha B Babannavar M.S.; C Karunakar Reddy; Alfred J Augustine; Shitalkumar G Sagari (Journal of Clinical and Diagnostic Research, 2015)
Gastrointestinal stromal tumours (GISTs) account for less than 3% of all gastrointestinal tract tumours and 5.7% of all sarcomas, and the majority of these tumours are gastric in origin. Patients commonly present with gastrointestinal bleeding or abdominal pain with 10-30% of patients presenting with symptoms of gastrointestinal obstruction. We report a rare case clinically presenting as gastric outlet obstruction, gastroscopy suspecting it to be organo-axial gastric volvulus, CECT(Contrast Enhanced Computerised Tomography) suggesting features of gastric malignancy (leiomyosarcoma) keeping the possibility of differential diagnosis of GIST. Eventually on exploratory laparotomy we discovered gastric outlet obstruction due to transpylorically herniated pedunculated polypoid GIST leading to gastroduodenal inussusception.